2013
DOI: 10.1021/jp4021883
|View full text |Cite
|
Sign up to set email alerts
|

Nb-Gateway for Hydrogen Desorption in Nb2O5 Catalyzed MgH2 Nanocomposite

Abstract: The state of Nb-contained catalysts in MgH 2 nanocomposites was investigated during the full cycle. X-ray diffraction (XRD) results showed that Nb 2 O 5 and Nb reacted with MgH 2 during ball-milling, forming NbH 2 and NbH, respectively. In the following dehydrogenation, the (di)hydride decomposed, and Nb was produced. Then NbH was generated in both samples after rehydrogenation. Similar composition in both samples suggests that the catalytic effect follows the same mechanism, the Nb-gateway model, in which Nb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…Ma et al [28] reported the presence of finely dispersed Nb nanocrystals with a typical size of~10e20 nm in a MgH 2 sample ball milled together with Nb 2 O 5 . It was suggested that Nb nanocrystals existing at the surface of MgH 2 particles behave as a gateway for the flow of hydrogen in and out of Mg/MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [28] reported the presence of finely dispersed Nb nanocrystals with a typical size of~10e20 nm in a MgH 2 sample ball milled together with Nb 2 O 5 . It was suggested that Nb nanocrystals existing at the surface of MgH 2 particles behave as a gateway for the flow of hydrogen in and out of Mg/MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The XPS study of Friedrichs suggested that Nb 2 O 5 reacts with MgH 2 and gradually undergoes reduction to form catalytically active compounds which in turn offer effective hydrogen diffusion pathways [13]. Recently Ma et al have identified the reduction of Nb 2 O 5 , resulting in the formation of 10e20 nm Nb nanocrystals in a ball milled MgH 2 eNb 2 O 5 mixture [14]. Based upon this finding they suggested that Nb nanocrystals may act as a gateway for the desorption of hydrogen which apparently leads to better system performance.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the formation reaction of MgeNbeO phase occurred in-situ, a situation where excess Mg is always present. As for example, references [7,14], and [15], respectively used the Nb 2 O 5 concentrations 2, 10 and 8 mol%. For a short note on the choice of the concentration of Nb 2 O 5 , see the Supplementary Information (note #1).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the number density of small MgH 2 crystallites increases in the hydrogenation process. According to the Nb-gateway model proposed in our previous work, 11) highly-dispersed tiny Nb in the sample works as a gateway for hydrogen transportation, facilitating hydrogen dissociation and recombination during the process. MgH 2 could rapidly nucleate near the site where the catalyst exists.…”
Section: Resultsmentioning
confidence: 99%
“…11) On the other hand, we have been pursuing for the direct observation of the process using transmission electron microscopy (TEM). In the previous observation, the dehydrogenation process of MgH 2 catalyzed with 10 mol% Nb 2 O 5 was monitored via high resolution transmission electron microscope (HRTEM).…”
Section: Introductionmentioning
confidence: 99%